2013
DOI: 10.1111/exd.12228
|View full text |Cite
|
Sign up to set email alerts
|

Hairless and the polyamine putrescine form a negative regulatory loop in the epidermis

Abstract: Hairless (HR) is a nuclear protein with co-repressor activity that is highly expressed in the skin and hair follicle. Mutations in Hairless lead to hair loss accompanied by the appearance of papules (atrichia with papular lesions) and similar phenotypes appear when the key polyamine enzymes ornithine decarboxylase (ODC) and spermidine/spermine N1-acetyltransferase (SSAT) are overexpressed. Both ODC and SSAT transgenic mice have elevated epidermal levels of putrescine, leading us to investigate the mechanistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Skin specimens were obtained at days 0, 3, 5, 12 and 18 postdepilation (p.d. ), representing the telogen, anagen II, anagen IV, anagen VI and catagen phases, respectively . Three mice per time point were sacrificed, and dorsal skin samples (0.3 cm × 0.5 cm) harvested from the depilated areas were fixed in 4% paraformaldehyde in phosphate‐buffered saline (PBS) or immediately frozen in liquid nitrogen at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Skin specimens were obtained at days 0, 3, 5, 12 and 18 postdepilation (p.d. ), representing the telogen, anagen II, anagen IV, anagen VI and catagen phases, respectively . Three mice per time point were sacrificed, and dorsal skin samples (0.3 cm × 0.5 cm) harvested from the depilated areas were fixed in 4% paraformaldehyde in phosphate‐buffered saline (PBS) or immediately frozen in liquid nitrogen at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have reported that polyamines play an important role in animal hair growth, that inhibition of polyamine synthesis regulates murine hair growth and that polyamines also help determine hair growth in sheep hair follicles . Recently, the correlation between hair loss and polyamines has received increasing attention . Polyamines are also associated with inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…HF cycling and hair growth are regulated in a myriad of ways via cytokines, growth factors, receptors and transcription factors (1,2). Uncontrolled signalling pathways resulting in overexpression and underexpression of HF proteins can cause severe hair growth abnormalities including hair loss (3,4).…”
Section: Introductionmentioning
confidence: 99%